Those who come and go, and sometimes, stay - Tjoa, Wei Lin (Nanyang Technological University, 2022)
Mark Twain mentions that whoever a man is is due to his make and influences by his surroundings and associations. Focusing on associations, Those Who Come and Go, and Sometimes Stay is an installation about the effects on one’s personality by the people they have met. How do people change as they meet others? Is there an idea of a “true self”?